Penanaman Pendidikan Ibadah Siswa di Sekolah Dasar Swasta Al-Ittihadiyah Bromo Medan - Ulandari .; Hadis Purba; Mohammad Al Farabi (CV. ITTC INDONESIA, 2024)
This research is entitled instilling Students Worship Education at Al-Ittihadiyah Bromo Private Elementary School, Medan. This research aims to determine the implementation of the worship program at SDS Al-Ittihadiyah, which incidentally is a public elementary school. However, with the implementation of this worship program, students are still found who like to speak harshly, hit their friends and fight. Therefore, this research is needed to find out the extent to which the program has a positive impact on student’s morals. This research uses a qualitative research method with a phenomenological approach. The data collection technique is observation, interviews, and document study. The data analysis technique involves reducing data, presenting data, and drawing conclusions. The results of this research reveal that the implementation of the worship program at Al-Ittihadiyah Bromo Medan Private Elementary School has had a positive impact on students. Some of these changes are that students become more disciplined, polite and obedient to teacher orders. As for other changes, students become happier doing worship and student activities can be directed towards positive things and away from negative things. Keywords: Planting, Worship Education, Elementary School Students